2014
DOI: 10.1177/1477153514548883
|View full text |Cite
|
Sign up to set email alerts
|

A light-emitting diode motorcycle low-beam headlamp based on a freeform reflector

Abstract: The illumination quality of a motorcycle lighting system is essential for safety and driving comfort. In this paper, we propose a light-emitting diode (LED) motorcycle low-beam headlamp based on a freeform reflector. The reflector is generated by a freeform optics design method. Then, the optical system is simulated by the Monte Carlo method using commercial optical tracing software. The low-beam headlamp is then fabricated and assembled into a physical object. Both the simulation and measurement results show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Therefore, we carried out some optical designs. 7,9,10,12,13 First, the optical axis of the entire optical system is set as the z -axis, so the plane XOY is the target lighting plane. Then, we start to mesh the lighting area, as shown in Figure 8.…”
Section: Design Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we carried out some optical designs. 7,9,10,12,13 First, the optical axis of the entire optical system is set as the z -axis, so the plane XOY is the target lighting plane. Then, we start to mesh the lighting area, as shown in Figure 8.…”
Section: Design Methodsmentioning
confidence: 99%
“…With the development of manufacturing technology, freeform optics is widely used in imaging 13 and in non-imaging optics systems. 410 Compared with the reflection cup design method, the projection system parts are small and compact. The light distribution has a clear cut-off line and a uniform light distribution, so it is increasingly used in LED motorcycle lighting.…”
Section: Introductionmentioning
confidence: 99%
“…We have reported a LED low-beam headlamp design based on a freeform reflector. 13 The experimental results showed that the illuminance distribution could satisfy the ECE Regulation R113 revision 2. In this paper, we provide a design for both low-beam and high-beam headlamps for motorcycles based on freeform micro-lenses.…”
Section: Introductionmentioning
confidence: 94%